Interpersonal Communication and the Application of Religious Values in Building Family Resilience in Mandailing Natal - Marlina, Marlina; Rambe, Elismayanti; Wahyuni, Rahmi; Fitri, Sari (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2024)
In today’s era of disruption, technology poses a challenge for families in maintaining effective communication, which is crucial for family well-being. Effective communication significantly impacts relationships, particularly within families. This study aims to explore how interpersonal communication, centered on religious values, shapes family resilience. This research employed a descriptive qualitative method, utilizing interview data collection, observations, and document studies. Data analysis was conducted using descriptive techniques. The findings revealed a rise in divorce rates and increased fragility of family values within the Mandailing Natal community. The pervasive influence of information technology has created barriers to interpersonal communication among families, leading to unfiltered exposure to information. Consequently, the community faces challenges in applying these values effectively. Moreover, negative impacts and strained relationships within families have worsened as a result.